A Diachronic Lexical Analysis of Little Women: Comparing The 1869 and 1970 Editions - Zahira Sufyan; Otong Setiawan Djuharie (PT. Padang Tekno Corp, 2025)
This paper provides a comprehensive comparative textual analysis of Chapter 1 of Louisa May Alcott's seminal novel, Little Women. The primary focus is a diachronic examination of lexical and orthographic variations between the original 1869 Roberts Brothers first edition and the 1970 Everyman's Library paperback edition, spanning a century of publication history. The central research problem addresses the process and implications of textual alteration in classic literature reprints. This study aims to identify, categorise, and analyse these changes to illuminate the editorial decisions, whether conscious or unconscious, that shape the evolution of a literary text for subsequent generations of readers. The methodology employed is a meticulous side-by-side comparative reading of the chapter, documenting discrepancies in vocabulary, spelling, punctuation, grammar, and capitalisation. The results indicate a consistent pattern of modernisation in the 1970 edition. Key findings include the substitution of colloquial or archaic vocabulary, the updating of orthography (e.g., ‘dont’ to ‘don’t’ ), and the modification of punctuation to align with contemporary conventions. These alterations, while enhancing immediate readability, subtly modify the original linguistic flavor, narrative rhythm, and historical context of Alcott's work. The preservation of certain authorial idiosyncrasies, such as character-specific misspellings, is also noted, suggesting a nuanced editorial framework. The study concludes that such textual evolution has a tangible impact on character voice and overall tone, underscoring the importance of edition selection in both academic and leisure reading.